140k views
4 votes
Verify that -(x+y)=(-x)+(-y) when x=3/4 and y=2/5

User Tejs
by
5.2k points

1 Answer

3 votes

Answer:

note that when opening the bracket the value outside the bracket with be used to multiply all the values inside the bracket... for example -(3/4+2/5) the (-) subtraction sign will be used to multiply all the values in the bracket including the addition sign therefore changing plus to minus

Verify that -(x+y)=(-x)+(-y) when x=3/4 and y=2/5-example-1
User Ilia Sidorenko
by
4.9k points